Advances in innovative delivery systems for antiglaucoma drugs. Issue 2 (21st March 2023) - Chen, XinYi; Shen, Ting
Abstract : Purpose of review: Currently, glaucoma treatment drugs are facing problems such as low bioavailability, poor patient compliance, discontinuous administration affecting the efficacy of intraocular pressure (IOP) lowering and chronic damage to the eye caused by side effects of drugs. In order to solve these problems and to better meet clinical needs, various new dosage forms have been developed and applied in the clinical setting. Recent findings: A number of nano formulations and extended-release gels are in successive animal trials, some tear plugs, implants and contact lenses are in clinical trials, and it is believed that more new carrier materials and formulations to improve the bioavailability of drugs are being developed. Summary: Novel delivery systems for antiglaucoma drugs offer patients more and better therapeutic options, and ongoing or completed studies are providing clear directions for subsequent research to improve clinical applications.